2018
DOI: 10.1038/s41577-018-0004-8
|View full text |Cite
|
Sign up to set email alerts
|

C-type lectins in immunity and homeostasis

Abstract: The C-type lectins are a superfamily of proteins that recognize a broad repertoire of ligands and that regulate a diverse range of physiological functions. Most research attention has focused on the ability of C-type lectins to function in innate and adaptive antimicrobial immune responses, but these proteins are increasingly being recognized to have a major role in autoimmune diseases and to contribute to many other aspects of multicellular existence. Defects in these molecules lead to developmental and physi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
457
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 521 publications
(460 citation statements)
references
References 172 publications
2
457
0
1
Order By: Relevance
“…Functional analysis suggested that reducing FAMK-1 phosphorylation of one lectin (CLEC-233) resulted in mild phenotypes in embryos analogous to those observed in famk-1Δ. Lectins are increasingly recognized as critical players in diverse aspects of multicellular life (Brown et al, 2018). In particular, there is growing evidence for potential functions for C-type lectins in bone mineralization and/or mineralized structure formation (Wewer et al, 1994;Mann and Siedler, 2006;Yue et al, 2016).…”
Section: Lectins: One Class Of Famk-1 Substratesmentioning
confidence: 98%
“…Functional analysis suggested that reducing FAMK-1 phosphorylation of one lectin (CLEC-233) resulted in mild phenotypes in embryos analogous to those observed in famk-1Δ. Lectins are increasingly recognized as critical players in diverse aspects of multicellular life (Brown et al, 2018). In particular, there is growing evidence for potential functions for C-type lectins in bone mineralization and/or mineralized structure formation (Wewer et al, 1994;Mann and Siedler, 2006;Yue et al, 2016).…”
Section: Lectins: One Class Of Famk-1 Substratesmentioning
confidence: 98%
“…Alternatively, the ITAM can be present in a receptor-associated signaling subunit. For example, in CD3 chains associated with the T-cell receptor (TCR), the CD79 chains associated with the B-cell receptor (BCR) and the FcRγ chain associating with the myeloid cell receptor Dectin-2 or the natural killer (NK) cell receptors NK1.1/Ly49D/Ly49H/NKG2D (2, 3). Upon receptor triggering, Src family kinases phosphorylate the ITAMs, thereby providing a docking site for Syk family kinases.…”
Section: Various Receptors Signal Via Carma/card Proteins and Malt1mentioning
confidence: 99%
“…CLRs are a superfamily of more than 1000 secreted and transmembrane proteins that contain one or more C-type lectin domains (CTLDs). Although CTLDs are responsible for the binding of carbohydrates by CLRs, they can also bind several chemically unrelated molecules including proteins, lipids, and inorganic materials [7]. In particular, some CLRs expressed mainly by myeloid cells recognize fungal cell wall polysaccharides.…”
Section: Clr Signaling and Antifungal Innate Immunitymentioning
confidence: 99%